Synthesis And Characterization Of Poly Ester Amide Polymer For Drug Delivery Applications - MANJUNATHA M; JAGADISH R.L; GOWDA D.V.; MOHAMMED S. KHAN (International Journal of Pharma and Bio Sciences, 2010)
Polymers are ideal class of materials to cover large application areas due to their light weight, biocompatibility, non-corrosive nature, chemical inertness, low cost and comparable densities with that of human organs. The usage of polymers is increasing day by day due to some of their special features which include higher strength to weight ratio, the ease of processability, low cost, light weight, inertness (in most cases), amenability to get a specific property etc. The present study aims for synthesis of biopolymer which is bio compatible and non toxic and which will envisages a tool for the drug delivery. Polymer is characterized by FTIR and DSC which shows presence of moiety present in required polymer. Acute toxicity testing is done in order to render the polymer acceptable for therapeutic use.